Fault-tolerant multilevel converter to feed a switched reluctance machine - Fernao Pires, Vitor (2022)
The switched reluctance machine (SRM) is one of the most interesting machines, being adopted for many applications. However, this machine requires a power electronic converter that usually is the most fragile element of the system. Thus, in order to ensure high reliability for this system, it is fundamental to design a power electronic converter with fault-tolerant capability. In this context, a new solution is proposed to give this capability to the system. This converter was designed with the purpose to ensure fault-tolerant capability to two types of switch faults, namely open- and short-circuit. Moreover, apart from this feature, the proposed topology is characterized by a multilevel operation that allows improvement of the performance of the SRM, taking into consideration a wide speed range. Although the proposed solution is presented for an 8/6 SRM, it can be used for other configurations. The operation of the proposed topology will be described for the two modes, fault-tolerant and normal operation. Another aspect that is addressed in this paper is the proposal of fault detection and diagnosis method for this fault-tolerant inverter. It was specifically developed for a multilevel SRM drive. The theoretical assumptions will be verified through two different types of tests, firstly by simulation and secondly by experiments with a laboratory prototype.